2023
DOI: 10.5603/ah.a2023.0009
|View full text |Cite
|
Sign up to set email alerts
|

The role of inflammatory biomarkers in the arterial hypertension

Abstract: Studies on both humans and animals have found evidence of a link between inflammation and hypertension (HTN).A lower serum calprotectin level was found to be independently related to HTN. The elevated ferritin-HTN link could be mediated by fatty liver disease and insulin resistance (IR). Similarly, fibrinogen was engaged in several processes that may increase the risk of HTN which including hemostasis, coagulation, and the proliferation of smooth muscle cells in the artery wall, and others. Procalcitonin monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…This result suggests that ALT may independently contribute to the development of hypertension. Although the precise mechanism behind this association remains unclear, some researchers suggest that ALT may cause oxidative stress, faster heart rate, increased arterial stiffness, and inflammation, which can damage blood vessels and lead to the development of hypertension 23,27–30 . Previous studies have shown that elevated GGT levels are a risk factor for high blood pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result suggests that ALT may independently contribute to the development of hypertension. Although the precise mechanism behind this association remains unclear, some researchers suggest that ALT may cause oxidative stress, faster heart rate, increased arterial stiffness, and inflammation, which can damage blood vessels and lead to the development of hypertension 23,27–30 . Previous studies have shown that elevated GGT levels are a risk factor for high blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise mechanism behind this association remains unclear, some researchers suggest that ALT may cause oxidative stress, faster heart rate, increased arterial stiffness, and inflammation, which can damage blood vessels and lead to the development of hypertension. 23,[27][28][29][30] Previous studies have shown that elevated GGT levels are a risk factor for high blood pressure. In their study, Stranges et al reported that GGT was a strong predictor of incidence over a 6-year follow-up period in a doseresponse relationship.…”
Section: Association Of Liver Enzymes With Incidence Of Hypertensionmentioning
confidence: 99%